Acupuncture with or without moxibustion for primary dysmenorrhea: A protocol for a systematic review and meta-analysis. Issue 38 (18th September 2020) - Zhou, Xingchen; Xiong, Jun; Chi, Zhenhai; Hua, Fanghui; Lu, Lunbin; Chen, Jun; Tang, Genhua; Zhu, Siyuan; Zhong, Zhiying; Guo, Han
Abstract: Background: Primary dysmenorrhea (PD) occurs during menstrual cramps, and there is currently no pathological evidence. This disease severely affects the daily lives of young women. Acupuncture (ACU) and moxibustion are an excellent way to relieve the pain of patients with PD. And it has been widely utilizing. However, the effectiveness and safety of ACU and moxibustion in treating patients with PD are not confirmed by a high-quality meta-analysis. This work aims to evaluate ACU's efficacy and safety with or without moxibustion in the management of PD. Methods: We will make a comprehensive retrieval in 9 databases as following: Embase; Cochrane Library; PubMed; Chinese databases SinoMed (previously called the Chinese Biomedical Database); Chinese National Knowledge Infrastructure; Chinese Scientific Journals Database; Wanfang Data. The time is limited from the construction of the library to August 2020. No restrictions about language and status. Our 2 authors will perform the selection of studies, the extraction of data, and the quality assessment with the risk of bias tool independently. We will use NoteExpressV3.2.0 and Excel2010 software to extract data. The content will be saved in electronic form. We will use the bias risk tool provided by the Cochrane Collaboration to evaluate the quality of the literature using RevMan 5.4 software. The primary outcome is the pain degree evaluation, including visual analog scale, numerical rating scale, Cox retrospective symptom scale, or any other scale used to evaluate the level of pain. Furthermore, the response rate involved an overall reduction in symptoms. The adverse effects and quality of life will be assessed as secondary outcomes. The risk ratio for dichotomous data and mean differences with a 95% confidence interval for continuous data will be adopted to express the effect and safety of ACU with or without moxibustion for PD. Results: The results of our study expect to provide high-quality, evidence-based recommendations on further treatment for clinicians. Trial registration number: INPLASY202080006. Conclusion: This study will provide scientific evidence of PD Systematic review.